2022
DOI: 10.3390/jof8010050
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Low-Cost Strategy to Improve Conidial Yield and Stress Resistance of Trichoderma guizhouense through Optimizing Illumination Conditions

Abstract: Light is perceived by photoreceptors in fungi and further integrated into the stress-activated MAPK HOG pathway, and thereby potentially activates the expression of genes for stress responses. This indicates that the precise control of light conditions can likely improve the conidial yield and stress resistance to guarantee the low cost and long shelf life of Trichoderma-based biocontrol agents and biofertilizers. In this study, effects of wavelengths and intensities of light on conidial yield and stress toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Light regulates important physiological and morphological processes of fungi 36 , 37 , 38 , 39 , 40 . Blue light can trigger photoconidiation of T. guizhouense , and this process relies on the blue light receptor BLR1 28 , 33 . The MAPK HOG signaling pathway is also involved in photoconidiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light regulates important physiological and morphological processes of fungi 36 , 37 , 38 , 39 , 40 . Blue light can trigger photoconidiation of T. guizhouense , and this process relies on the blue light receptor BLR1 28 , 33 . The MAPK HOG signaling pathway is also involved in photoconidiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study in Trichoderma guizhouense also demonstrated that the MAPK HOG1 translocates from the cytoplasm into the nucleus upon blue light stimulus, consistent with the finding in A. nidulans that SakA (HogA) accumulates in the nucleus after red light exposure 13 , 28 . Additionally, the MAPK HOG1 controls a large proportion of blue light‐regulated genes, including stress‐related genes encoding catalases, photolyases, heat shock proteins, and hydrophobins 28 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…However, how Basidiomycetes sense different environmental stresses during fruiting body development is still unclear [ 49 ]. In yeasts and filamentous fungi, MAPK cascades are important signaling pathways to respond to environmental stresses and regulate processes, such as the cell cycle, reproduction, cell differentiation, morphogenesis, and stress response [ 25 , 28 , 30 , 51 , 52 , 53 , 54 ]. The signal induced by environmental stresses is transmitted by the sequential phosphorylation of a basic array of three proteins, often termed MAPKKK, MAPKK, and MAPK, [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAPK pathways are evolutionarily conserved signaling modules in eukaryotic organisms [ 25 ]. In fungi such as Saccharomyces cerevisiae and Aspergillus fumigatus , the MAPK pathways respond to a variety of environmental signals, such as cell wall stress, light, nitrogen, and carbon deprivation and high osmolarity, and regulate the expression of genes associated with cell differentiation and development [ 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precise control of light conditions can likely improve the conidial yield and stress resistance to guarantee the low cost and long shelf life of Trichoderma-based biocontrol agents and biofertilizers. In a study [ 10 ], effects of wavelengths and intensities of light on conidial yield and stress tolerance to osmotic, oxidative and pH stresses in Trichoderma guizhouense were investigated. The authors found that blue light increased the conidial yield more than 1000 folds as compared to dark conditions and simultaneously enhanced conidial stress resistance.…”
mentioning
confidence: 99%